Becoming the supervisor : achieving your company's mission and building your team - Alley, Hugh R. (New York : Routledge, 2020)
"This book is the story Trevor who works as one of the production team in a small company that makes toy boats. He is thrust into the role of supervisor unexpectedly when his general manager reacts to his constant suggestions of how things could be better. When the GM gets ill, Trevor struggles for several months. Then a new GM arrives, and the core of the book is Trevor's growth under the coaching of his new GM, Julie. The conclusion of the book is Trevor's promotion to Production Manager when Julie sees that he has been able to both achieve the mission of the organization and develop his people. The reader takes away four key ideas: 1) Front-line leadership skills are not too complicated to learn. 2) These skills are something that they can develop in themselves, regardless of what their organization does. 3) Tools and skills are there to help solve real business problems; implementing the tools is not a strategy. 4) In your role as supervisor (directing or responsible for others) you have to look after the mission of the company AND look after your people - doing only one is not an option. Essentially, this book is intended to give hope to a new supervisor or team lead. They will finish the book knowing that the skills they need can be learned and aren't that difficult. It is designed to introduce the central skills that any supervisor has to be able to accomplish at least with a basic working competency: instructing, leading, and making improvements in their own area. It introduces some of the more widely-used tools that a new supervisor may run into. More importantly, it ties these tools and skills to solving particular problems. Readers will understand that the tools are not important for their own sake, but only to the extent that the tools serve the larger objective of the organization. The book is designed to give the reader an entertaining and hopeful story about the very difficult transition from worker to supervisor, from being one of the crew to directing the crew. It is an emotionally tough transition, and the idea that someone could see a model of how it can work out will be helpful to folks new in a leadership role. Finally, the book provides a reference to other sources of information that will let the reader extend their learning about each of the tools or skills referenced in the book"--
List of Figures. List of Tables. Preface. Acknowledgements. About the Author. Chapter 1 You Be The Supervisor. Chapter 2 The First Four Months. Chapter 3 A New Boss. Chapter 4 The First Meetings. Chapter 5 The Observations. Chapter 6 The Morning Meeting. Chapter 7 He Quit - Learning to Instruct. Chapter 8 Making Improvements. Chapter 9 Improvements in My Area. Chapter 10 The Problem Child. Chapter 11 The Accident. Chapter 12 Collisions. Epilogue.
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Problem solving; Decision making; Teams in the workplace -- Management; Organizational effectiveness; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Quality Control